Post-implantation Deformation of Titanium Rod and Cobalt Chrome Rod in Adolescent Idiopathic Scoliosis - Ung, Sia; BB, Tan; Yian Yeong, Teo; CC, Wong (2019)
Introduction: Post-implantation rod deformation is anticipated in scoliosis surgery but the difference in rod deformation between titanium and cobalt chrome rod has not been elucidated. This study aims to compare the difference in rod deformation between two groups. Materials and Methods: Twenty-one adolescent idiopathic scoliosis (AIS) patients were recruited from a single center. The over-contoured concave rods were traced prior to insertion. Post-operative sagittal rod shape was determined from lateral radiographs. Rod deformation was determined using maximal rod deflection and angle of the tangents to rod end points. The differences between pre- and post-operative rod contour were analysed statistically. Rod deformation and thoracic kyphosis between two types of implants were analysed. Results: Both rods exhibited significant change of rod angle and deflection post-operatively. Curvature of the titanium rod and cobalt chrome rod decreased from 60.5° to 37°, and 51° to 28° respectively. Deflection of titanium rod and cobalt chrome rod reduced from 28mm to 23.5mm and 30mm to 17mm respectively. There was no significant difference between titanium and cobalt chrome groups with regard to rod angle (p=0.173) and deflection (p=0.654). Thoracic kyphosis was increased from 20° to 26° in titanium group but a reduction from 25° to 23° was noticed in cobalt chrome group, but these findings were not statistically significant. Conclusion: There was no statistical difference in rod deformation between the two groups. Thus, the use of titanium rod in correction of sagittal profile is not inferior in outcome compared with cobalt chrome but with lower cost.